A study on the factors that influencing employees` attitudes toward organizational change / Farah Adilla Abd Rahman … [et al.] - Abd Rahman, Farah Adilla; Md. Shahid, Khairiyah; Ahmad, Nasyrah; Razali, Nabila Najat; Mohd Shazali, Nurliyana; Abdullah, Nurul Atika; Haris, Siti Melinda (Faculty of Administrative Science and Policy Studies, 2012)
The purpose of this study is to identify the factors that influencing employees` attitudes toward organizational change in public sector. The study had been carried out in Melaka state government at Kompleks Seri Negeri, Ayer Keroh. This research is written with the objectives to examine the relationship between factor influencing employees` attitudes toward organizational change, to identify the most positive employees` attitude towards organizational change and to provide recommendations regarding organizational change to the public sector. The sample size of this study was 123 employees who come five different departments which are Department of Human Resource Management, Department of Corporate Communication, Department of Management Information System, Department of Library Management and Department of K-economy. Questionnaires were distributed to employee based on the simple random sampling method and proportionate sampling. The findings reveal that all of the factors (internal communications, work-related values, emotional Intelligence and organizational commitment) influence employees` attitude toward organizational change at varying degree.